Prevalence of depression and its risk factors among patients with chronic obstructive pulmonary disease in a tertiary level hospital in West Bengal, India - Bhowmik, Kalyan; ., Moniruzzaman; Adhikari, Anjan; Choudhury, Shahnaz; Ahmed, MSA Mansur (South East Asia Journal of Public Health, 2013)
In recent years, chronic obstructive pulmonary disease (COPD) has increased several folds in the developing coun-tries and the disease is accompanied with several co-morbidities among which depression is a major one. Still now there is a lack of data regarding the prevalence and risk factors of depression among the patients with COPD in In-dia. The aim of the study is to assess the prevalence of depression and associated risk factors in patients with COPD in Kolkata, India. In this cross-sectional study, 214 COPD patients were selected by purposive sampling at OPD of Pulmonary Medicine, RG Kar Medical College, Kolkata, India. The patients were diagnosed and grouped into dif-ferent stages of COPD by clinical examination and spirometry. A questionnaire was administered among the respon-dents to collect the data regarding their socio-demographic conditions followed by Patient Health Questionnaire 9 (PHQ-9) to measure the level of depression. The mean age of the respondents was 59.37±11.37 years and 99% were male. The proportion of depression among patients with COPD was 86%. Among the respondents, 36.9% had mod-erately severe depression, 32.2% had moderate depression and 6.1% had severe depression. The risk factors of de-pression among COPD patients were urban residence (OR=4.79, p=0.02), income group of 5000-9999 Rupees per month (OR=18, p=0.38), teetotalers (OR=8.36, p=0.02), Stage 2 COPD (OR= 83, p=0.001) and onset of COPD ?70 years of age (OR=20, p=0.02). The study showed that more than 8 out of 10 COPD patients and it can be considered very high proportion. The study highlight the importance of routine screening for depression of all COPD patients in all healthcare settings and implementation of effective strategies for proper prevention and management of depres-sion in those patients. DOI: http://dx.doi.org/10.3329/seajph.v2i2.15942 South East Asia J Public Health | Jul-Dec 2012 | Vol 2 Issue 2 | 34-40